Jogas Recepcijas Problēmas Rietumu Pasaulē: The Problems of Reception of Yoga in the Western World. - Taivāne, Elizabete (Cel̜š, 2016)
The article is dedicated to the different aspects and modes of reception of yoga in the Western world. According to the sociological surveys taking place in Latvia and Lithuania during the time period from 1997 until now yoga and Indian religious ideas are rather popular in the West and even influence Christian religious practice and worldview. Nevertheless the reception of Indian religiosity does not mean a replacement of Christian worldview by the Indian one rather it means a problematic clash of different cultural paradigms and destruction of Western ethics and religious symbols. The incompatibility of anthropological models in Christianity and Hinduism is the reason why it would be important to restore Western spirituality from inside, translating the traditional Christian anthropological categories in the language of contemporaneity.